Matched sibling donors versus alternative donors in allogeneic hematopoietic stem cell transplantation for pediatric severe aplastic anemia in México. Issue 8 (September 2015) - Rodríguez, Laura; González-Llano, Óscar; Villarreal, Laura; Gómez-Almaguer, David; Ortiz, Magdalena; Olaya-Vargas, Alberto; Pérez-García, Martín; Ruíz-Argüelles, Guillermo J.; Ruíz-Delgado, Guillermo J.; Muñiz, Teodoro; De-Diego, José; Reyes, Nancy; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives Hematopoietic stem cell transplantation (HSCT) from a matched sibling donor (MSD) is the preferred initial treatment for children with severe aplastic anemia (SAA). Unfortunately, only about 30% of patients have a suitable human leukocyte antigen-matched sibling. Methods We have analyzed the outcome of 42 patients who received HSCT (22 MSD and 20 alternative donors (AD)) for SAA at the seven major pediatric HSCT centers in Mexico between 2001 and 2013. Results With a median follow-up of 30 months (range, 0.4–144), the 5-year overall survival in children transplanted from MSD was 86.4 + 7.3 vs. 49.5 + 11% for children after AD-HSCT (P = 0.013). The cumulative incidence of treatment-related mortality (TRM) was in the MSD-HSCT 9.1 + 3.9% vs. 47.6 + 9.1% in the AD-HSCT context (P = 0.007). Infectious complications contributed to death (91%) of most patients who received AD-HSCT. Discussion Even when the results of patients given MSD-HSCT are adequate, there is still much room for improvement particularly in children allografted with AD and in the supportive care. The development of an economicwise designed prospective project with MSD or matched unrelated donor HSCTs as a first line of treatment of children with SAA as a unified national trial could address these issues.